Book Reviews: Hinson, Glenn E., "Love at the Heart of Things" - Muers, Rachel (Quaker studies, 2000)
HINSON, Glenn E., Love at the Heart of Things (Wallingford, PA: Pendle Hill Publications; Nashville, TN: The Upper Room Books, 1998), pp. 392. $ 16.50. ISBN 0-87574-929-1 (Pendle Hill), 0-8358-0860-2 (Upper Room Books)